Contextual Influences on the Individual Life Course: Building a Research Framework for Social Epidemiology - Juan Merlo (Psychosocial Intervention, 2011)
Individual health is not only individual responsibility, but also depends on the social contexts that condition the individual across the life course. However, while it is of high public health relevance to identify these contextual influences, they still remain poorly understood, and the research performed so far has suffered from severe limitations. This paper presents a research agenda for social epidemiology that underlines a number of novel concepts, ideas, and unanswered questions deserving future investigation. The paper presents a conceptual framework intended to organize the investigation of geographical, socioeconomic, and cultural disparities in health. This framework identifies five main areas of research: (1) identifying the relevant contexts that influence individual health by measuring general contextual effects, (2) measuring contextual characteristics, the specific effects of these characteristics on individual health and their underlying cross-level mechanisms, (3) investigating general and specific contextual effects from a longitudinal, a life-course perspective and across generations, (4) developing quasi-experimental methods (e.g., family-based designs) for the analysis of causal effects in contextual analyses, and (5) using the achieved scientific knowledge for planning and evaluating interventions. The proposed framework emphasizes that future research in social epidemiology should question the current means-centric reductionism that is mostly concerned with the identification of (contextual) risk factors, and it stresses the need to deliberately investigate determinants of variance. In fact, social epidemiology is not only interested in increasing the (mean) health of the population, but also in understanding and decreasing inappropriate health inequalities (variance).